Accessibility for Persons with Disabilities in Employment Opportunities in Private Companies: A Case Study of Indonesia - Baby Poernomo; Charles Magwari Omboto; Jeruth Ngonzi Tinka (Yayasan Ilomata, 2022)
The absorption of workers with disabilities in Indonesia is still limited. The companies argue that it is difficult to meet accessibility for disabled workers because it requires a lot of funds, for instance facilities that need to be made so that the workplace accessible for people with disabilities. This research is aimed at answering the questions of how the accessibility of persons with disabilities in employment opportunities in private companies in Indonesia, what obstacles encountered by persons with disabilities who work in private companies, and how the solutions are provided so that persons with disabilities have easy access to work in private companies. This is a qualitative research with a case study approach. The data collection in this study used semi-structured interviews with 20 people with disabilities consists of 10 people with disabilities who were rejected by companies and 10 people with disabilities who had been accepted to work but finally decided to quit. In this study, a public policy expert was also interviewed to obtain data on how policies related to persons with disabilities were implemented. The results of this study indicate that there are still many people with disabilities who are rejected to work by the companies. If anyone is already working, eventually they have to resign considering the unequal treatment they have received, both from the leaders and fellow employees. However, until now there has never been a company that got a sanction even though the regulations regarding the treatment of persons with disabilities have been affirmed in Law Number 8/2016. Therefore, stricter supervision is needed for private companies so that they not only fulfill the quota of 1% of employees with disabilities out of the total number of employees, but also pay attention and treat employees with disabilities the same as other employees.